A constituição discursiva de subjetividades de alunos e alunas da EJA em narrativas docentes - Almeida, Patrícia da Silva (2015)
This research is subject to subjectivity constitution of students of the Youth and Adult Education (EJA) in discursive practices that permeate the teacher narratives (as), who work in a public school in the municipality of Mamanguape. Asks-: How the speeches teachers constitute the subjectivities students face the singularities of this type of education? Is outlined as the main objective of this work: to analyze the extent to which the discursive practices that make up the accounts of (as) teachers (as) the EJA contribute or collaborate for the construction of subjectivities of (the) students (as). Theoretical and methodologically, the research shall be founded in French discourse analysis of the concepts (AD), such as speech, interdiscourse and discursive memory, in Foucault's theories about the relationships of power and modes of subjectivity. The research comes within the framework of Applied Linguistics and adopts the concept of language as a social practice. Qualitative and interpretative nature, are adopted as methodological questionnaires and interviews procedures. By analyzing the linguistic materiality of this research, we infer that the discursive constitution of teacher subjectivities in narratives of teachers and teachers of the Youth and Adult Education takes place through the games of truth that permeate the socio-historical context and the relationships of power and discipline passing in the educational universe. At the end of the investigation, presents the actions that make up the proposed intervention and its possible outcomes